Tolerance induction to stress caused by lavender (Lavandula angustifolia) extracts in the microalga Dunaliella salina through metabolic modifications and Î²-carotene production - Sahar Mazang-Ghasemi; Alireza Einali; Jafar Valizadeh; Meisam Noroozifar (Zīst/shināsī-i Giyāhī-i Īrān, 2016)
The inhibitory or stimulatory effect of one plant on other plant species through the released chemical compounds into the environment, known as allelochemicals, is called allelopathy. In the present study, effect of aqueous extracts of lavender (Lavandula angustifolia) leaves on growth pattern and ability of β-carotene production in unicellular green alga, Dunaliella salina was investigated. Based on these results, phenolics content and antioxidant capacity of the extracts was relatively low. Treated cultures with extract concentrations of 1, 2, 3 and 4 % showed that the process of cell division was ceased because of extracts phytotoxicity. However, the chlorophyll and β-carotene concentration pronouncedly increased in phytotoxin-treated cells, so that the highest of these values were detected in 3 % extracts-exposed cells. Percentage change of all three fresh weight, total sugar and protein between 0 and 48 h of phytotoxins treatment was significantly increased concurrently with increasing dose of extracts. These results suggest that D. salina tolerate allelochemicals-induced stress by metabolic modifications. Therefore, phytotoxins-tolerance mechanisms in D. salina are associated with physiological and metabolic adjustments by allocating the carbon flux to the synthesis of the sugars, chlorophyll and β-carotene, which induce phytotoxins stress tolerance in this alga.